2016
DOI: 10.1111/1365-2745.12643
|View full text |Cite
|
Sign up to set email alerts
|

Plant–soil feedbacks: role of plant functional group and plant traits

Abstract: Summary1. Plant-soil feedback (PSF), plant trait and functional group concepts advanced our understanding of plant community dynamics, but how they are interlinked is poorly known. 2. To test how plant functional groups (FGs: graminoids, small herbs, tall herbs, legumes) and plant traits relate to PSF, we grew 48 grassland species in sterilized soil, sterilized soil with own species soil inoculum and sterilized soil with soil inoculum from all species, and quantified relative growth rate (RGR), specific leaf a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
267
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(297 citation statements)
references
References 64 publications
(145 reference statements)
16
267
4
Order By: Relevance
“…These patterns of host specificity are consistent with results of plant-soil feedback studies that have shown reduced plant growth on soil with a history of plants of the same species or functional group compared to the average community soil (e.g. Cortois et al 2016;Hendriks et al 2013;Mangan et al 2010;Petermann et al 2008). It is, however, crucial to reveal the (fungal) actors and their functional role in grassland plant communities, if we want to increase our understanding of the myriad of plantfungal interactions belowground.…”
Section: Host Specificitysupporting
confidence: 81%
See 1 more Smart Citation
“…These patterns of host specificity are consistent with results of plant-soil feedback studies that have shown reduced plant growth on soil with a history of plants of the same species or functional group compared to the average community soil (e.g. Cortois et al 2016;Hendriks et al 2013;Mangan et al 2010;Petermann et al 2008). It is, however, crucial to reveal the (fungal) actors and their functional role in grassland plant communities, if we want to increase our understanding of the myriad of plantfungal interactions belowground.…”
Section: Host Specificitysupporting
confidence: 81%
“…by comparing plant growth on soils with and without soil biota (e.g. Cortois et al 2016;Hendriks et al 2015b;Kos et al 2013;McCarthy-Neumann and Ibáñez 2013;Wubs and Bezemer 2018). For example, Schnitzer et al (2011) grew plant communities in field and sterilized field soil.…”
Section: Agalinis Gattingeri Aletris Farinosa Gentiana Alba Liatris Smentioning
confidence: 99%
“…Garnier et al, 2007;de Bello et al, 2010). However, recently trait based approaches are being used to predict plant legacy effects in soil and subsequent plant responses (Orwin et al, 2010;Ke et al, 2015;Cortois et al, 2016). To date most PSF experiments have focused on plant biomass as sole measure of plant responses to soil legacies.…”
Section: Plant Traits and Remote Sensingmentioning
confidence: 99%
“…Recent research has shown that some structural root traits show a global organization, as plants adapted to dry and seasonal conditions generally have thinner roots than plants adapted to humid, non-seasonal conditions . In turn, this variation in structural root traits will also affect mycorrhizal dependency and colonization of the plant species, as thin roots can replace the functions otherwise performed by mycorrhizal fungi (Cortois et al 2016;Ma et al 2018). Potentially, adaptations to specific environments and soil communities may also, at least in part, explain differences in plant-soil interactions observed in Chapter 6.…”
Section: Future Directionsmentioning
confidence: 99%
“…Soil biota play important roles in plant community dynamics by causing positive or negative plantsoil feedback effects (Kardol, Bezemer & van der Putten 2006;Van Der Heijden, Bardgett & Van Straalen 2008), which differ among plant species (Cortois et al 2016). Plant-soil feedbacks on conspecifics vary with phylogenetic distance (Anacker et al 2014) and are affected by plant origin (Klironomos 2002) when phylogenetically diverse plant species were examined.…”
Section: Introductionmentioning
confidence: 99%